Atmospheric variability in precipitation associated with on-shore and off-shore breezes in northeastern Pará - Germano, Michell Fontenelle; Vitorino, Maria Isabel; Costa, Gabriel Brito; Souza, Adriano Marlison Leão de; Souto, Jefferson Inayan de Oliveira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
Sea (onshore) and land (offshore) breezes and their role in precipitation on the coast of Pará were investigated. We retrieved wind data (direction and velocity) and precipitation at 10 minute intervals from the micrometeorological tower located at the Universidade Rural da Amazônia UFRA experimental site at Cuiarana in the municipality of Salinópolis, Pará state. We used satellite images from the Geostationary Operational Environmental Satellite (GOES) satellite in the visible channel and CPC MORPHing technique (CMORPH) data for spatial visualization of precipitation. Results show that the breezes are more intense during the rainy season (March) than during the dry season (August). Observed local precipitation, which may be related to sea breezes, showed a higher frequency during the late afternoon and early evening. These results allow us to evaluate the influence of sea breezes on costal local precipitation.